Eldecalcitol prevented OVX-induced osteoporosis through inhibiting BMSCs senescence by regulating the SIRT1-Nrf2 signal - Yuying Kou; Yuying Kou; Xing Rong; Xing Rong; Rong Tang; Rong Tang; Yuan Zhang; Yuan Zhang; Panpan Yang; Panpan Yang; Hongrui Liu; Hongrui Liu; et al. (Frontiers Media S.A., 2023)
Background: Aging and oxidative stress are considered to be the proximal culprits of postmenopausal osteoporosis. Eldecalcitol (ED-71), a new active vitamin D derivative, has shown a good therapeutic effect on different types of osteoporosis, but the mechanism is unclear. This study focused on exploring whether ED-71 could prevent bone loss in postmenopausal osteoporosis by regulating the cell senescence of bone mesenchymal stem cells (BMSCs), and explaining its specific mechanism of action.Materials and methods: An ovariectomized (OVX) rat model was established and 30 ng/kg ED-71 was administered orally once a day. The weight of rats was recorded regularly. Micro-computed tomography (CT) and histochemical staining were used to evaluate bone mass, histological parameters, and aging-related factors. Rat bone mesenchymal stem cells were extracted and cultivated in vitro. Aging cells were marked with senescence-associated β-gal (SA-β-gal) dyeing. The mRNA and protein levels of aging-related factors and SIRT1-Nrf2 signal were detected by RT-PCR, Western blot, and immunofluorescence staining. The reactive oxygen species (ROS) levels were detected by DCFH-DA staining.Results: Compared with the Sham group, the bone volume of the ovariectomized group rats decreased while their weight increased significantly. ED-71 prevented bone loss and inhibited weight gain in ovariectomized rats. More importantly, although the expression of aging-related factors in the bone tissue increased in the ovariectomized group, the addition of ED-71 reversed changes in these factors. After extracting and in vitro culturing bone mesenchymal stem cells, the proportion of aging bone mesenchymal stem cells was higher in the ovariectomized group than in the Sham group, accompanied by a significant decrease in the osteogenic capacity. ED-71 significantly improved the bone mesenchymal stem cells senescence caused by ovariectomized. In addition, ED-71 increased the expression of SIRT1 and Nrf2 in ovariectomized rat bone mesenchymal stem cells. Inhibition of SIRT1 or Nrf2 decreased the inhibitory effect of ED-71 on bone mesenchymal stem cells senescence. ED-71 also showed a suppression effect on the reactive oxygen species level in bone mesenchymal stem cells.Conclusion: Our results demonstrated that ED-71 could inhibit the cell senescence of bone mesenchymal stem cells in ovariectomized rats by regulating the SIRT1-Nrf2 signal, thereby preventing bone loss caused by osteoporosis.